Pengaruh Quality of Work Life Terhadap Employee Engagement Pada PT. Honda Sanggar Laut Selatan Cabang Kota Palopo - Rahmy Rezky Amelia; Andini; Muh. Ar’at Ramadhan; Juliawan Syam; Erwina; Munawir (STIM-LPI Makassar, 2023)
Comfort in the company is related to the success of the company. A good work environment needs to be considered to create quality of work life so as to help foster the desire of each employee to remain in the company and achieve company goals. Factors of quality of work life (quality of work life) become a supporter or obstacle that can affect employee engagement (employee engagement) in the company. This research was conducted at one of the current HONDA Car Dealers in Makassar, which is engaged in Sales, Spare Parts and Service (3S), namely PT. Honda of the South Sea Studio, Palopo City Branch. When the research was conducted February - March 2023 with a questionnaire collection technique on 30 respondent from employees of PT. Honda Palopo Branch of the South Sea Studio. The sample selection method used is saturated sampling. Data analysis techniques using descriptive analysis and simple linear regression analysis. Based on data processing, the result can be obtained that the quality of work life has a significant effect on employee engagement.